Evaluasi Switch Therapy Antibiotik pada Pasien Pneumonia di RSUP Dr. M. Djamil Padang - Sondang Khairani S.Farm., M.Farm., Apt (Jurnal Penelitian Farmasi Indonesia, 2015)
The ideal route of administration for any medication is one that achieves serum concentration sufficient to produce the desired effect withoutproducing undesired effect. Patients may be concidered candidates for switching from intravenous to oral therapy once the patient has shown clinicalimprovement and is medically stable. Purpose of this study is the evaluation of selection antibiotics and timeliness to switch therapyfrom iv to oralantibiotics therapy.A prospective observation study, data were collected from all hospitalized patients with community-acquired pneumonia at internal medicinedepartment and respiratory care department at Dr. M. Djamil Public Hospital in Padang Indonesia from September until November 2013receivedantibioticswitchtherapy. Objective criteria were used to define time to switch therapy. Result showed, 49 patients fulfill inclusive criteria in thisresearch, 41 patients from internal medicine department and 8 patients from respiratory care department. All use ceftriaxone intravena, but 32 (65%)patients wrong in switched to oral therapy antibiotics, where 23 to cefixime, 7 to azithromycin, 1 to cefadroxyl and 1 to amoxcillin + clavulanic acid.Only 17 patients (35%) with prompt conversion of intravena antibiotic therapy to oral, 12 to ciprofloxacin and 5 to levofloxacin, only 12 patients rightin time to conversion intravena to oral antibiotics, with time to switch therapy was the fifth days. 49 patients have been discharged in goodconditionand doctor's approval.